Breast conserving therapy for DCIS—Does size matter?. Issue 1 (27th May 2014) - Kantor, Olga; Winchester, David J.; Rubio, Isabel T.; Dixon, J. Michael
<x xml:space="preserve">Abstract</x> The incidence of ductal carcinoma in situ has increased dramatically with the use of screening mammography. Most patients can be considered for breast conserving therapy, depending upon patient and pathologic variables. In addition to other factors, tumor size is important to provide proper patient selection for breast conserving surgery and predict risk of local recurrence. J. Surg. Oncol. 2014 110:75–81. © 2014 Wiley Periodicals, Inc.